Production and characterization of heat treated OSB made of Pinus taeda - Felippe Silva, Joao Vitor [UNESP]; Campos, Cristiane Inacio de [UNESP]; Ferreira, Bruno Santos [UNESP]; Felippe Silva, Maria Fernanda [UNESP] (Univ Estadual Maringa, Pro-reitoria Pesquisa Pos-graduacao, 2019)
Oriented strand board (OSB) panels, like plywood, are destined for structural use. Both of them may undergo preservative treatments that extend their lifetime and increase their resistance against weathering and xylophagous agents. One possibility is a heat treatment where the wood is exposed to temperatures above 130 degrees C (403 K), which causes chemical, physical, and mechanical changes. The aim of this work was to produce OSB made of Pinus taeda thermally treated without replacement of atmosphere for an inert gas. The physical properties of density, moisture content, and thickness swelling in water immersion for 24 hour were evaluated. The mechanical properties of static bending were determined by the modulus of elasticity (MOE), modulus of rupture (MOR), and an internal bond test. Boards were heattreated at 160, 180, and 200 degrees C (433, 453 and 473 K), and panels were produced with heat-treated strands at 160 and 180 degrees C (433 and 453 K). The heat treatment of boards did not affect mechanical properties compared to the control treatment. The thermal treatment of strands reduced the physical and mechanical performances of the panels.
Keywords: thermic treatment; physical and mechanical characterization; structural board; phenol formaldehyde resin